MOVO AC: AN INTERACTIVE PHYSICS LEARNING MEDIUM TO HELP STUDENTS UNDERSTAND THE CONCEPT OF ELECTRIC POTENTIAL - Wahyu Dwi Handari (Jurnal Pembelajaran Sains, 2020)
The problems in physics learning classes are complex. Difficulties in understanding the concept of physics become the biggest obstacle. One of those difficulties is a lack of learning media especially a prop to learn an abstract static electricity concept. This research and development was designed to create a prop of learning media in the form of a feasible tool to show that distance can affect the electrical potential. In this study, ADDIE cosisting of Analysis, Design, Develop, Implementation, and Evaluation were employed. The developed teaching aids were tested in two test classes at SMAN 1 Tulungagung. Results in validity data with vaues of 94% with very good category.  The classical completeness of the learning outcomes of students increased from 83% to 92% of the 72 students who were spreaded in class XII MIPA 1 and XII MIPA 3. Meanwhile, from the questionnaire that was distributed, it was found that the response of students who stated it was good to use was 93%. Overall, it can be concluded that movo AC is worthy to use as learning media in static electricity especially to show that the number of distance can affect the electrical potential.